Resin composites direct restoration of enamel structural defects - case report - Irina-Maria Gheorghiu; Sanziana Scarlatescu; George Nicola; Alexandru-Andrei Iliescu; Ioanina Parlatescu; Ioana Suciu; Paula Perlea (Amaltea Medical Publishing House, 2022)
During dentition development stages, various defects of the dental structures can appear and can be in shape, number, position, structure. The latter primarily affect the aesthetic appearance, but also the other functions of the dentomaxillary system, when the severity of the lesions is important. Enamel hypoplasia in the frontal area of dental arches, with moderate extension of defects, can be easily treated with modern resin composite materials using adhesive technique, by direct restorations. In this way, the coronal morphological integrity and the harmonious dento-facial appearance are restored. Restorations for this type of dental lesions need to be carefully monitored and retreatment performed if necessary.